2014
DOI: 10.1038/ncomms6543
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of single-molecular chirality from achiral reactants

Abstract: The synthesis of enantiopure molecules from achiral precursors without the need for pre-existing chirality is a major challenge associated with the origin of life. We here show that an enantiopure product can be obtained from achiral starting materials in a single organic reaction. An essential characteristic of this reaction is that the chiral product precipitates from the solution, introducing a crystal–solution interface which functions as an asymmetric autocatalytic system that provides sufficient chiral a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 38 publications
1
60
0
Order By: Relevance
“…Previously, we showed that experiments involving a lower initial concentration of achiral reactants lead to the formation of a smaller number of crystals. 19 This in turn leads to a shorter deracemization time as less crystals have to undergo deracemization. However, crystal nucleation affects the deracemization rate in a more complex way.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previously, we showed that experiments involving a lower initial concentration of achiral reactants lead to the formation of a smaller number of crystals. 19 This in turn leads to a shorter deracemization time as less crystals have to undergo deracemization. However, crystal nucleation affects the deracemization rate in a more complex way.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…19 The achiral precursors reversibly reacted with 1,8-diazabicyclo [5.4.0]undec-7-ene (DBU) as an achiral catalyst in solution to give both enantiomers of the product, which in turn rapidly crystallized to form a racemic crystal−solution system. Because of the applied grinding, the initially racemic conglomerate crystals were subsequently deracemized through Viedma ripening in which the final configuration of the product was found to be randomly either pure (R)-1 or pure (S)-1.…”
Section: ■ Introductionmentioning
confidence: 99%
“…31 In the same year, Soai et al showed that an initial small amount of chiral product can be amplified to single chirality. 35 It was found that the product amine forms racemic conglomerate crystals while in solution it can racemise through a reversible aza-Michael reaction. 33 These results underline the fact that the synthesis of an enantiopure product from achiral reactants without pre-existing enantioenrichment still is extremely difficult to achieve in solution.…”
Section: (4) Recent Examplesmentioning
confidence: 99%
“…The deracemisation of isoindolinones by means of attrition has been described [92]. Attrition-induced deracemisation has been applied in a Mannich reaction [93] and represents another example of absolute asymmetric synthesis [94]. Temperature programming has been used as an aid in attrition-induced der-acemisation to deracemise a conglomerate, 1-(4-chlorophenyl)-4,4-dimethyl-2-(1H-1,2,4-triazol-1-yl)pentan-3-on [95].…”
Section: Discussionmentioning
confidence: 99%